177k views
2 votes
PLEASE HELP PLEASE HELP PLEASE HELP PLEASE HELP

PLEASE HELP PLEASE HELP PLEASE HELP PLEASE HELP-example-1
User Dvska
by
5.4k points

1 Answer

3 votes

Answer:

x = - 5 , x = 7

Explanation:

to find the zeros, let y = 0 , that is

x² - 2x - 35 = 0

consider the factors of the constant term (- 35) which sum to give the coefficient of the x- term (- 2)

the factors are - 7 and + 5 , since

- 7 × + 5 = - 35 and - 7 + 5 = - 2 , then

x² - 2x - 35 = (x - 7)(x + 5) = 0

equate each factor to zero and solve for x

x + 5 = 0 ⇒ x = - 5

x - 7 = 0 ⇒ x = 7

User Soumen
by
6.2k points